Gender and identity construction : women of Central Asia, the Caucasus and Turkey. - Gunes-Ayata, Ayse; Acar, Feride (Social, economic, and political studies of the Middle East and Asia;, 2000)
This volume deals with issues and problems of national and gender identity in Central Asia, the Caucasus and Turkey. Articles discuss experiences and position of women vis--vis state intervention, economic, political and cultural change, in both public and private spheres of life. In the book the real life conditions and experiences of women are analyzed on three complementary levels. The first of these is the economic and institutional circumstances shaped by structural adjustment policies, globalization and transnational policies. The second is realities of everyday life, particularly pertaining to family, religion, tradition and education. The third level is that of politics and ideology where national and nationalist discourses often build on the gender identity shaped by the economic and social levels. The book does not only present a cross cultural analysis of women's position in the region but also reflects the varied perspectives of female scholars from many different countries and disciplines -- Description de l'éditeur.